Does the Incorporation of ESG Criteria Lead to Superior Financial Performance? - Saarteinen, Salla (My University, 2019)
During the past decade, socially responsible investing has become a rapidly growing phenomenon in the financial industry that has caught the attention of socially and environmentally conscious investors and firms. The emergence of socially responsible investing has allowed investors to combine their personal preferences and values with their investment decisions. This has led to the exponential growth of SRI funds and firms publishing non-financial information. The aim of this thesis is to examine the possible abnormal returns socially aware investors are provided from incorporating ESG criteria to their investment decisions. The impact of incorporating ESG criteria is measured and analyzed using the CAPM and Fama-French three factor model for over 200 listed companies in the Nordic market. Three large European stock markets are used as a comparison to examine whether the Nordic market has varying return patterns from the rest of the European markets. Thomson Reuter’s ASSET 4 ESG scores are obtained to select companies with ESG activities for the period from 2000-2016. Regression models measure the abnormal returns provided by the synthetically constructed ESG and non-ESG portfolios. Empirical findings suggest that the Nordic ESG portfolio is able to earn insignificantly higher abnormal returns that the non-ESG during the whole sample period. However, when splitting the sample period to crisis and non-crisis periods, the ESG portfolio significantly outperforms the non-ESG portfolio. Incorporating ESG criteria to investment decisions in the Nordic market during market crises seems to be associated with higher abnormal returns. These findings contribute to existing literature by examining ESG performance in the Nordic countries.
Keywords: ESG; socially responsible investing; sustainability; investment performance; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|